META ANALISIS: PENGARUH INSTRUMENT ASSESSMENT PADA MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN 4C - Nurul Azmi; Festiyed Festiyed (Postgraduate, University of Mataram, 2023)
This study aims to 1) analyze the effect of the project-based learning model in terms of 4C skills, 2) analyze the influence of the project-based learning model in terms of education level, and 3) analyze the influence of the project-based learning model in terms of learning materials. The type of research applied to this study is meta-analysis. The results of this study are: 1) the project-based learning model has an influence to improve 4C skills with an average effect size on critical thinking skills of 2.23 high categories, creative thinking skills of 0.92 high categories, communication skills of 2.43 high categories and collaboration skills of 4.79 high categories; 2) the project-based learning model has an influence on improving 4C skills at the education level, namely junior high school, high school and university with an average effect size at each level, namely 1.6 high categories at the junior high level, 1.05 high categories at the high school level and 2.9 high categories at the higher education level; and 3) the project-based learning model has an effect on improving 4C skills with the highest average effect size on substance change material of 5.04 high categories and the lowest average effect size in motion dynamics material of 0.18 small categories.